Implementasi Pembelajaran Tahfiz Al-Quran Mahasantri Pondok Pesantren Nurul QuranTangerang Selatan - Bobi Erno Rusadi (UMSU, 2018)
Pesantren Nurul Quran is an Al-Quran boarding school devoted to students. To enter this pesantren, mahasantri candidates are required to go through recruitment stages including the Quran recitation test and interviews. Students who study at the pesantren consist of students of the Al-Quran Higher Education Institute (PTIQ) and also students of Syarif Hidayatullah State Islamic University in Jakarta. This study aims to describe the implementation of tahfiz learning in Pesantren Nurul Quran. The research method in the research is qualitative descriptive with data analysis of Mile and Huberman models. The results of this study are: a) The method used in tahfiz learning is the method of talaqqi and takrir, b) Murajaah activity is carried out in four parts, namely personal murajaah, murajaah by guidance, murajaah in the tahajud, and murajaah weekly, c) Evaluation in tahfiz learning is done regularly on the last week of each month. While the difficulties faced by mahasantri in memorizing the Quran are a) the difficulty of memorizing new verses that are not understood in its meaning, b) Busyness in activities outside the pesantren, which is between preparing lectures and memorizing the Quran at the pesantren.